Associations Between Sibling Relationship Quality and Friendship Quality in Early Adolescence: Looking at the Case of Twins. (8th March 2016) - Bekkhus, Mona; Brendgen, Mara; Czajkowski, Nikolai O.; Vitaro, Frank; Dionne, Ginette; Boivin, Michel
Abstract : Bidirectional pathways between twin relationship quality and friendship quality were investigated in a large longitudinal twin cohort. We examined negative and positive relationship features in 313 monozygotic (MZ) twins and 238 same-sex dizygotic (DZ) twins from ages 13 to 14 years, using latent structural modeling. Results showed stronger stability of the twin relationship quality compared to friendship quality. Positive features in the sibling relationship were associated with increased positive features in the relationship with the best friend a year later. In contrast, no significant association between negative sibling relationship features and change in negative friendship quality features was found. These findings speak to the important role of the sibling relationship in the development of good quality friendship relations in twins.